Using Graphical organizers in the teaching process of ICT - Asiya Ibragimovna Tureniyazova (Research in Social Sciences and Technology- OpenED Network, 2019)
To date, hundreds of advanced teaching methods have been developed, such as game methods, problem-based learning methods, and information and communication technologies are widely used in education. Most of these technologies are based on the principles of student-centred and participatory learning. These interactive methods allow the learner to master the necessary professional knowledge, skills and competencies under the managerial guidance of a teacher. In this article, the author would like to share her experience of using one of such techniques - graphic organizers - in teaching the subject of computer science and information technologies. The graphic organizers as supportive tools for teaching and learning, their use and types are described. Examples of graphic organizers for learning IT and Information security, drawn using IT, are given.